Hodnoceni investičního záměru - Handrla, Aleš (Vysoké učení technické v Brně. Fakulta podnikatelská, 2023)
Práce má za úkol zhodnotit plánovaný investiční záměr společnosti SVOBODA-stavby s.r.o. ve věci zakoupení nového stroje, který má přispět k úspoře finančních nákladů firmy. Práce rozebere základní teoretické poznatky týkající se investičního záměru společnosti, charakterizuje společnost a klasifikuje výslednou účinnost záměru. Na závěr práce zhodnotí záměr společnosti, zdali realizovat zmíněný projekt a vymezí doporučené návrhy na zlepšení.

The task of the bachelor's thesis is to evaluate the planned investment of SVOBODA-stavby s.r.o. in the matter of the purchase of a new machine, which is supposed to contribute to saving the company's financial costs. The thesis analyzes the basic theoretical knowledge regarding the company's investment plan, then characterizes the company and classifies the overall effectiveness of the plan. At the end of the work, it will evaluate the planned investment of the company on the realization of the project and define recommended suggestions for improvement.
The Evaluation of the Investment
Keywords: investice; hodnocení investice; stavební stroj; stavební společnost; riziková investice; Investment; investment evaluation; construction machine; construction company; risky investment